Implementation of Islamic religious education in the era of independent learning - Rosyidi, M. Nurul Ardi; Suwendi, Suwendi (UIR Press, 2026)
The implementation of Indonesia's Merdeka Curriculum has transformed educational practices by promoting learner-centred pedagogy, instructional flexibility, and meaningful learning experiences. However, limited empirical evidence explains how these principles are enacted in Islamic Religious Education (IRE), a subject that integrates cognitive, moral, and spiritual development within formal schooling. This study aims to examine the implementation, instructional strategies, and challenges of IRE learning under the Merdeka Curriculum while exploring how learner-centred pedagogy is translated into classroom practice. Employing a qualitative descriptive design, data were collected through semi-structured interviews, classroom observations, and document analysis involving school principals, IRE teachers, students, and school policymakers. The findings reveal that the implementation of the Merdeka Curriculum has encouraged teachers to adopt contextual, flexible, and student-centred learning through differentiated instruction, project-based activities, and opportunities for learner autonomy and creativity. Nevertheless, its implementation remains constrained by limited instructional time, persistent teacher-centred beliefs, inadequate professional readiness, and insufficient institutional support. The novelty of this study lies in conceptualising the implementation of the Merdeka Curriculum in IRE as a process of reconstructing learner agency within faith-based education, rather than merely introducing curricular innovation. However, the findings are limited to a single institutional context and therefore should be interpreted cautiously. The study implies that successful implementation requires sustained professional development, supportive educational policies, and collaborative stakeholder engagement to foster transformative, learner-centred IRE that promotes both academic achievement and character formation.